To solve this equation for x, we can start by finding the common base for both sides of the equation.
First, rewrite 4 as 2^2:
(2^2)^x - 1/2 = 2x^2
Now, use the property (a^m)^n = a^(m*n) to simplify the left side:
2^(2x) - 1/2 = 2x^2
Next, multiply both sides by 2 to get rid of the denominator:
2 * 2^(2x) - 1 = 4x^2
Now, rewrite 2 * 2^2x as (2^1 * 2^2x) using the property a^m * a^n = a^(m + n):
2^(1 + 2x) - 1 = 4x^2
Simplify further:
2^(2x + 1) - 1 = 4x^2
Add 1 to both sides:
2^(2x + 1) = 4x^2 + 1
Now, rewrite the right side as 2^(2) using the property a^(loga(b)) = b:
2^(2x + 1) = 2^(2)
Now, since the bases are the same, we can set the exponents equal to each other:
2x + 1 = 2
Solve for x:
2x = 1
x = 1/2
Therefore, the solution to the equation is x = 1/2.
4^x-1over2 =2x^2
1 answer